2023
DOI: 10.1289/ehp11372
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures of Youth Exposure to Mixtures of Per- and Polyfluoroalkyl Substances: A Multi-Cohort Study

Abstract: Background: Exposure to per- and polyfluoroalkyl substances (PFAS) is ubiquitous and has been associated with an increased risk of several cardiometabolic diseases. However, the metabolic pathways linking PFAS exposure and human disease are unclear. Objective: We examined associations of PFAS mixtures with alterations in metabolic pathways in independent cohorts of adolescents and young adults. Methods: Three hundred twelve overweight/obese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 133 publications
0
23
0
Order By: Relevance
“…In previous work, we reported on the maternal and fetal metabolomic associations with prenatal exposure to single PFAS chemicals and adverse birth outcomes. , The present analysis builds on this work by examining the effects of a PFAS mixture. Similar to our approach, a 2023 study also examined the impact of a PFAS mixture on the plasma metabolome of adolescents and young adults enrolled in the Study of Latino Adolescents at Risk (SOLAR) and Southern California Children’s Health Study (CHS) . Across our study and the study conducted within SOLAR and CHS, amino acids and fatty acids critical to energy production and endocrine signaling for healthy growth and development in early life were consistently perturbed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous work, we reported on the maternal and fetal metabolomic associations with prenatal exposure to single PFAS chemicals and adverse birth outcomes. , The present analysis builds on this work by examining the effects of a PFAS mixture. Similar to our approach, a 2023 study also examined the impact of a PFAS mixture on the plasma metabolome of adolescents and young adults enrolled in the Study of Latino Adolescents at Risk (SOLAR) and Southern California Children’s Health Study (CHS) . Across our study and the study conducted within SOLAR and CHS, amino acids and fatty acids critical to energy production and endocrine signaling for healthy growth and development in early life were consistently perturbed.…”
Section: Discussionmentioning
confidence: 96%
“…Our work has also demonstrated that short-chain PFAS, such as perfluorohexanesulfonic acid (PFHxS), perturb the maternal metabolome through biosynthetic and bioenergetic pathways while legacy long-chain PFAS, such as PFOS and PFOA, tend to dysregulate signaling pathways . Despite awareness that individuals are exposed to multiple PFAS chemicals, the cumulative effects of PFAS on the human metabolome remain largely unknown due to the complexity of integrating high-dimensional data across statistical approaches . The assessment of biological responses to PFAS exposures and resulting health outcomes is further complicated by the lack of sensitive and specific biomarkers, interindividual heterogeneity in toxicokinetics, and involvement of numerous endogenous pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these metabolic genes, their products, and endogenous metabolites using omics approaches, including genomics, transcriptomics, proteomics, and metabolomics, can identify metabolic processes that are important during different life stages in normal and adverse health conditions 3 . These molecular omics approaches are discovering new insights into how metabolic processes are altered by diseases, toxic exposures and baseline genetic variations, enabling new prevention and therapeutic strategies for human diseases [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted metabolomics is a discovery-based technique that comprehensively assesses metabolic profiles and pathways . In tandem with statistical tools like metabolome-wide association studies (MWAS) and pathway enrichment analysis, relations between exposures to PFAS and hundreds to thousands of metabolites and their corresponding biological pathways can be investigated. As such, untargeted metabolomics is being increasingly used to identify metabolites and pathways associated with human exposure or disease …”
Section: Introductionmentioning
confidence: 99%
“…While numerous statistical methods have been developed to quantify the potential effects of chemical mixtures, few studies have evaluated the impact of PFAS mixtures on the fetal metabolome. Understanding the impact of PFAS exposures on the fetal metabolome is important because PFAS can cross the placenta, and the fetus may be more sensitive to environmental exposures compared to later life stages . Furthermore, the investigation of chemical mixtures is critical, given that PFAS exposure does not occur in isolation.…”
Section: Introductionmentioning
confidence: 99%